Modeling stakeholders for information systems design processes - Ballejos, Luciana Cristina (2011)
In the software engineering area, stakeholders play a significant role in requirements elicitation and validation. Moreover, all the project management is integrally affected by stakeholders' perspectives and their participation. This effect is strengthened when projects involve several organizations. Thus, a clear and explicit representation of the stakeholders and their attributes is required in order to achieve their effective management. The integration of this representation with other models capturing the knowledge of engineering design processes can be of great utility in software development projects. In this sense, this article describes the construction of an integrated model for representing stakeholders in information systems design processes. This proposal considers diverse attributes related to stakeholders and gives information for performing quantitative calculations about their interest and influence over the project. Thus, more inclusive experiences of the information systems development can be supported, even more if contexts with the participation of several organizations are considered.